TEACHING ENGLISH IN PRESCHOOL EDUCATIONAL ORGANIZATIONS BY USING ART THERAPY - Aziza Khayitova (Web of Journals Publishing, 2025)
In an increasingly globalized world, early childhood English language education has gained significant importance. Preschool represents a foundational stage for language acquisition due to children's cognitive flexibility and heightened receptivity to new stimuli. Simultaneously, the role of emotional and psychological development in education has been underscored by various pedagogical frameworks. Art therapy, originally a clinical tool for enhancing mental health through creative expression, is now gaining attention as a pedagogical method in early childhood education. This article explores the integration of art therapy into English language teaching (ELT) in preschool settings. It analyzes theoretical foundations, practical strategies, case studies, and challenges while presenting the benefits of this integrative approach.
Keywords: Art therapy, language acquisition, mental health, Integrative pedagogy, cognitive flexibility